Estrategias de resolución de problemas para mejorar las Capacidades Cognitivas e Investigativas en los estudiantes del 5° Grado de Educación Secundaria área CTA - Componente física en la Institución Educativa "Clemente López Montalván" del distrito de Calzada - Calderón Majuan, Deonel (2008)
The investigation(research) named strategies of resolution of problems to improve the cognitive capacities and investigativas in the students of S 0 degree of secondary education CTA's area - component Physical, in the Educational lnstitution "Clemente Lopez Montalván" of the district of causeway, has for aim(lens) determine that the strategies of resolution of problems will improve significantly the Cognitive Capacities and investigativas of the students of 5° degree of Secondary Education area CTA - component Physics, in the Educational lnstitution "Clemente Lopez Montalván" of the district of Causeway. From the description and explanation of the phenomenon of study based on the theory of the processing of the information of Newell and Simon, on the theory Piagetiana of the cognitive development, on Vygotsky's theory on the cognitive development and in Ausubel's theory on the cognitive development; there is hipotetizado that the strategies of resolution of problems will improve significantly the cognitive capacities and investigations(researches) in the students of 5° degree of Secondary Education area CTA - component Physics, in the Educational lnstitution "Clemente Lopez• Montalván" of the district of Causeway. With the intention of verifying the hypothesis, there has been gathered information of 41 units of analyses, to which, by means of the technology (skill) of the written evaluation, a written test (proof) applied type to them questionnaire, which has a significant reliability, to S % of the level of significancia, as (according to) chi squared calculated (18,91) major that chi squared tabulated (16,92). Tried the information, by means of the comparison of averages across measurements paired of the pre and posttest (postproof) of group of study, with t calculated (33,93) major that t tabulated (1,68), allows to establish that the strategies of resolution of problems improve significantly the cognitive capacities and investigativas in the Students of 5° degree of-Secondary Education area-CTA component Physica in the Educational lnstitution "Clemente Lopez Montalván" of the district of Causeway